2021
DOI: 10.3390/biom11030358
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C (APC) and 3K3A-APC-Induced Regression of Choroidal Neovascularization (CNV) Is Accompanied by Vascular Endothelial Growth Factor (VEGF) Reduction

Abstract: The activated protein C (APC) ability to inhibit choroidal neovascularization (CNV) growth and leakage was recently shown in a murine model. A modified APC, 3K3A-APC, was designed to reduce anticoagulant activity while maintaining full cytoprotective properties, thus diminishing bleeding risk. We aimed to study the ability of 3K3A-APC to induce regression of CNV and evaluate vascular endothelial growth factor (VEGF) role in APC’s activities in the retina. CNV was induced by laser photocoagulation on C57BL/6J m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…As we observed robust inflammation on days 4–7 after CNV induction ( Figure 1 , Figure 2 and Figure 3 ), we used a treatment regimen of 2 consecutive intravitreal injections of 1 µg/µL/eye 3K3A-APC, administered on days 4 and 7 post-CNV induction. The concentration of 3K3A-APC was chosen based on previously performed studies [ 18 , 19 ]. Then, 7 days after the last treatment (on day 13), an in-vivo injection of fluorescein isothiocyanate (FITC)-dextran was performed to mark retinal blood vessels fluorescently.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we observed robust inflammation on days 4–7 after CNV induction ( Figure 1 , Figure 2 and Figure 3 ), we used a treatment regimen of 2 consecutive intravitreal injections of 1 µg/µL/eye 3K3A-APC, administered on days 4 and 7 post-CNV induction. The concentration of 3K3A-APC was chosen based on previously performed studies [ 18 , 19 ]. Then, 7 days after the last treatment (on day 13), an in-vivo injection of fluorescein isothiocyanate (FITC)-dextran was performed to mark retinal blood vessels fluorescently.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, our group is the only one studying the effects of 3K3A-APC in the retina [ 18 , 19 ]. We previously showed that intravitreal (IVT) treatment with 3K3A-APC inhibits CNV growth and significantly reduces VEGF levels at CNV sites [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from its anticoagulant effects, APC also displays cytoprotective properties, such as blocking inflammatory cytokine release, 128 maintaining endothelial integrity and protecting cells from apoptosis. 129 , 130 So decreased plasma levels of APC are strongly linked with prognosis. Although controversial, APC has been used in severe sepsis.…”
Section: Neutrophils and Nets Induce A Pro‐coagulant Endothelial Cell...mentioning
confidence: 99%
“…Moreover, blocking endothelial NF‐κB signalling inhibits TNF‐α converting enzyme activity which is responsible for EPCR shedding, reducing plasma plasminogen activator inhibitor type‐1 level and restoring plasma level of APC 22,127 (Figure 4). Aside from its anticoagulant effects, APC also displays cytoprotective properties, such as blocking inflammatory cytokine release, 128 maintaining endothelial integrity and protecting cells from apoptosis 129,130 . So decreased plasma levels of APC are strongly linked with prognosis.…”
Section: Neutrophils and Nets Induce A Pro‐coagulant Endothelial Cell...mentioning
confidence: 99%